Exploration of some mechanisms involved in blinking to visual sexual stimuli - Felipe, Abraham I.; Mahl, George F. (1969)
This experiment (ɑ) tested the hypothesis that visual sexual stimuli would increase the rate of blinking and (b) explored some possible mechanisms involved in the relationship between such a conditioning experiment was run using 40 Ss, 20 of whom were conditioned with the use of sex pictures and the rest with the use of landscape scenes as the UCS. An auditory stimulus was used as CS for 10Ss of each group; a visual stimulus was used as CS for the remaining Ss. The sexual pictures elicited significantly more blinks than the landscapes, and both visual and auditory CS elicited more blinks when conditioned to the sexual pictures than when they were conditioned to the landscapes. The number of blinks elicited by the visual CS was not significantly different from that elicited by the auditory CS when both stimuli were conditioned to the sexual pictures. These results suggested that ɑ)the effect of the sexual pictures on arousal level is a critical factor in producing an increased blink rate and(b)the sensory modality of the arousing stimulus is not critical. It is possible, however, that the latter might have only been due to the number of acquisition trials used.
Includes bibliographical references (page 30).